Microresonators: A New Route for Fabricating On‐Chip Chalcogenide Microcavity Resonator Arrays (Advanced Optical Materials 7/2014). Issue 7 (15th July 2014) - Aktas, Ozan; Ozgur, Erol; Tobail, Osama; Kanik, Mehmet; Huseyinoglu, Ersin; Bayindir, Mehmet
<x xml:space="preserve">Abstract</x> Chalcogenides are promising materials for photonics due to their extraordinary optical properties. In order to achieve their full technological exploitation, they must be manufactured in photonic devices with various geometries necessitated by their unique optical functionalities. On page 618, M. Bayindir and co‐workers develop a new route for the fabrication of on‐chip photonic elements. This novel technique provides a low‐cost, high‐yield production method with a compatible and extendable integration phase. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>